Analisis Yuridis Perspektif Keamanan Maritim Nasional dalam Menghadapi Ancaman Hibrida Global (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Indonesia's maritime security faces increasingly complex challenges due to the rise of hybrid threats that combine traditional and non-traditional elements. One of the main threats is the shadow fleet, operating covertly with unregistered ships, evading detection, and exploiting weaknesses in maritime surveillance to engage in illegal activities such as smuggling, illegal transshipment, and unlawful exploitation of natural resources. This phenomenon exacerbates Indonesia's maritime security situation, particularly in strategic areas like the Natuna Sea and the Sunda Strait, which are vulnerable to geopolitical conflicts and overlapping territorial claims. Additionally, transnational crimes such as piracy, drug trafficking, and human trafficking further undermine security in Indonesian waters. To address these threats, Indonesia needs to strengthen its maritime surveillance capacity by adopting advanced technologies such as early detection sistems and the Automatic Identification Sistem (AIS), as well as enhancing coordination between maritime agencies like Bakamla and the Indonesian Navy (TNI AL) to improve responses to harder-to-detect threats. Moreover, international cooperation with neighboring countries and regional maritime organizations like ASEAN must be bolstered to tackle cross-border threats. Strengthening surveillance, modernizing technology, and fostering more integrative maritime diplomacy will be crucial in safeguarding Indonesia's maritime sovereignty and ensuring the stability of this increasingly strategic maritime region.